2017
DOI: 10.1021/acs.jpclett.7b01584
|View full text |Cite
|
Sign up to set email alerts
|

Route to Stable Lead-Free Double Perovskites with the Electronic Structure of CH3NH3PbI3: A Case for Mixed-Cation [Cs/CH3NH3/CH(NH2)2]2InBiBr6

Abstract: During the past year, halide double perovskites attracted attention as potential lead-free alternatives to Pb-based halide perovskites. However, none of the compounds discovered so far can match the optoelectronic properties of MAPbI (MA = CHNH). Here we argue that, from the electronic structure viewpoint, the only option to make Pb-free double perovskites retaining the remarkable properties of MAPbI is to combine In and Bi as B and B cations, respectively. While inorganic double perovskites such as CsInBiX we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
90
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(93 citation statements)
references
References 67 publications
0
90
0
Order By: Relevance
“…[203] Particularly, they found that the B(I)-on-B(III) and B(III)-on-B(I) cation antisites create deep states in the bandgap (Figure 17e), which may cause significant recombination, detrimentally affecting the carrier lifetime and V OC , as is the case of Cu 2 ZnSn(Se,S) 4 . [202] Copyright 2017, American Chemical Society. Overall, it seems quite challenging to support highefficiency solar cells with Pb-free halide double perovskites.…”
Section: D a 2 B(i)b(ii)x 6 Halide Double Perovskitesmentioning
confidence: 99%
“…[203] Particularly, they found that the B(I)-on-B(III) and B(III)-on-B(I) cation antisites create deep states in the bandgap (Figure 17e), which may cause significant recombination, detrimentally affecting the carrier lifetime and V OC , as is the case of Cu 2 ZnSn(Se,S) 4 . [202] Copyright 2017, American Chemical Society. Overall, it seems quite challenging to support highefficiency solar cells with Pb-free halide double perovskites.…”
Section: D a 2 B(i)b(ii)x 6 Halide Double Perovskitesmentioning
confidence: 99%
“…[184] For instance, a mixed A-cation double perovskite, (Cs/MA/ FA) 2 InBiBr 6 , was predicted to have comparable stability with MAPbI 3 . [184] For instance, a mixed A-cation double perovskite, (Cs/MA/ FA) 2 InBiBr 6 , was predicted to have comparable stability with MAPbI 3 .…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%
“…The organic cation based double perovskites have better thermal stability than their MAPbX 3 counterparts. [184] Copyright 2017, American Chemical Society. [154] The thermal analysis (Figure 15c,d) shows that (MA) 2 AgBiBr 6 can be stable up to ≈550 K with a heating rate of 10 K min −1 .…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%
“…However, Xiao et al205 used a combination of theoretical and experimental study to show that Cs 2 InBiCl 6 and Cs 2 InSbCl 6 were unstable due to spontaneous oxidation of In + into In 3+ . Lately, Volonakis et al206 proposed the rule of designing a useful double perovskite material: mimicking the electronic structure of MAPbI 3 . To stabilize the double perovskite structure of A 2 In + Bi 3+ X 6 , they suggested the use of mixed‐A‐site‐cation double perovskite (Cs/MA/FA) 2 InBiBr 6 rather than all‐inorganic double perovskites.…”
Section: Lead‐free Halide Hybrid Perovskite and Related Absorbersmentioning
confidence: 99%